The Impact of Self-Efficacy on Students' Mathematical Understanding - Rajab, Rahman; Fahinu, Fahinu; Lambertus, Lambertus; Zulfaidil, Zulfaidil (Jurnal Karya Pendidikan Matematika, 2024)
This study aims to describe the self-efficacy and mathematical understanding abilities of students at SMP Negeri 1 Kontukowuna and to analyze the influence of self-efficacy on the mathematical understanding abilities of these students. The population of this study consists of all 47 seventh-grade students at SMP Negeri 1 Kontukowuna. The sample was determined using a total sampling technique. Data analysis techniques include descriptive analysis and inferential analysis. Data collection techniques involve using a self-efficacy questionnaire and a mathematical understanding test. The results of the data analysis showed that 8.51% of students have very high self-efficacy, 19.15% have high self-efficacy, 42.55% have moderate self-efficacy, 27% have low self-efficacy, and 2.13% have very low self-efficacy. Furthermore, 17.02% of students have high mathematical understanding abilities, 70.21% have moderate mathematical understanding abilities, 12.77% have low mathematical understanding abilities, and no students fall into the very high or very low categories. Finally, it was found that there is a significant positive influence of self-efficacy on the mathematical understanding abilities of seventh-grade students at SMP Negeri 1 Kontukowuna, with a significance level of . The regression equation is , and the coefficient of determination () is 0.223, which means that self-efficacy (X) contributes 22.3% to mathematical understanding (Y), while the remaining 77.7% is influenced by other factors outside the independent variable (X) not discussed in this study.